Morphological Characterization and Seed Germination Study of Wild Banana Musa acuminata var. flava (Ridl.) Nasution - Trimanto Trimanto; Elga Renjana; Dewi Ayu Lestari; Elok Rifqi Firdiana; Shofiyatul Mas’udah; Apriyono Rahadiantoro; Linda Wige Ningrum; Lia Hapsari (Journal of Tropical Biodiversity and Biotechnology, 2022)
Wild bananas provide important genetic materials for further banana improvement, therefore they need to be conserved and studied. This study aimed to describe morphological characteristics of plant and seed and also to study the seed germination of wild banana M. acuminata var. flava (Ridl.) Nasution. The morphological characteristics were observed descriptively by referring to the descriptor for banana. The internal and external morphology of the seeds were observed using a digital microscope. The germination testing was carried out by a completely randomized design, using fresh seeds extracted from a bunch of fruits with two ripeness levels i.e. fully-ripe (yellow peel) and under-ripe (green-yellow peel). The data resulted was then analyzed using an independent t-test. The results showed that M. acuminata var. flava is characterized as a perennial herb; pseudostem height ≥3 m; male bud like a top with prominent green-yellow bracts; fruit curved and tasted mild-sweet when ripe. The seed is angular with wrinkled surface, and dark brown-black color when ripe. The longitudinal section showed parts of the seeds comprising the seed coat, outer and inner integument, embryo, endosperm, chalazal mass, micropyle cap and channel. The seeds are classified as orthodox, with hypogeal type and gradual germination pattern. The seeds extracted from fully-ripe fruit germinated faster with higher germination percentage and growth variables (root number and plant height). Thus, it is suggested to use physiologically mature seeds (seeds from fully-ripe fruits) which should be separated from the seeds of under-ripe fruits to lower the heterogeneity.